2018
DOI: 10.1089/pho.2018.4453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photobiomodulation on Degranulation and Number of Mast Cells and Wound Strength in Skin Wound Healing of Streptozotocin-Induced Diabetic Rats

Abstract: We conclude that photobiomodulation and CM alone and or in combination significantly accelerated the healing process in a rat with a diabetic and ischemic wound, and significantly decreased the total number of mast cells and degranulation of mast cells. We suggest that the increased number of type 2 mast cells in the control group adversely affected the tensiometric properties of wounds in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…It is possible that circulating immune cells (mast cells, macrophages, etc. ), stimulated by PBM, [81][82][83][84] could transduce protective signals from distal tissues to sites of injury such as the brain, heart, or gut.…”
Section: Photobiomodulationmentioning
confidence: 99%
“…It is possible that circulating immune cells (mast cells, macrophages, etc. ), stimulated by PBM, [81][82][83][84] could transduce protective signals from distal tissues to sites of injury such as the brain, heart, or gut.…”
Section: Photobiomodulationmentioning
confidence: 99%
“…Studies on MSCs in tissue engineering have been gaining prominence in recent decades, especially in the reconstruction of dermal tissues due to the high capacity for self‐renewal, proliferation, and differentiation in several types of cells, such as epithelial cells (Caliari‐Oliveira et al, 2016). Thus, in an attempt to accelerate healing processes, ensuring a good tissue quality, studies have explored the association of PBM with MSCs in an attempt to create a low‐cost alternative, easy application as a treatment for cutaneous wounds (Amini et al, 2018; Bagheri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, since tryptase contributes to the pathogenesis of diabetes and its complexities, aiming MCs as a new remedy for diabetes needs more investigations [12]. In this context, it has been reported that the increased numbers of total MC density and degranulation in diabetic animals negatively affected the potentiometric properties of their skin wounds [13][14][15]. Recently, Wygrecka et al have suggested that MCs might provide to the fibrotic course by encouraging local fibroblasts in the lung, therefore leading to the pathogenesis of the illness [16].…”
Section: Discussionmentioning
confidence: 99%